Rizal and Philippine nationalism - Romero, Ma. Corona S.; Mendoza, Amelia S. ;De Jesus, Christopher A. ([Manila, Philippines] : [Thinkbook Enterprises], 2009)
The book is updated with information both on global and Philippine Affairs.
1. Concepts and values : Strategies toward a better Filipino nation -- 2. Human and cultural Constituents in the maze of Emancipation -- 3. Heroic leadership and Rizal -- 4. The Debacle of Rizal's Death -- 5. His Novels -- 6. His essays -- 7. His Poems -- 8. Bonifacio and Other national leaders -- 9. Toward Unity and Peace, Justice and prosperity with health and Nutrition. -- 10. Philippine Nationalism Today.
Includes bibliographical references and index.
Keywords: RIZAL, JOSE P